Computed Regioselectivity and Conjectured Biological Activity of Ene Reactions of Singlet Oxygen with the Natural Product Hyperforin. (16th February 2017) - Abramova, Inna; Rudshteyn, Benjamin; Liebman, Joel F.; Greer, Alexander
Abstract: Hyperforin is a constituent of St. John's wort and coexists with the singlet oxygen sensitizer hypericin. Density functional theory, molecular mechanics and Connolly surface calculations show that accessibility in the singlet oxygen "ene" reaction favors the hyperforin "southwest" and "southeast" prenyl (2‐methyl‐2‐butenyl) groups over the northern prenyl groups. While the southern part of hyperforin is initially more susceptible to oxidation, up to 4 "ene" reactions of singlet oxygen can take place. Computational results assist in predicting the fate of adjacent hydroperoxides in hyperforin, where the loss of hydrogen atoms may lead to the formation of a hydrotrioxide and a carbonyl instead of a Russell reaction. Abstract : This is a theoretical study of "ene" reactions of singlet oxygen with hyperforin. Shown is a brief compass to give directions of prenyl locations where the southern part of the natural product is more susceptible to singlet oxygenation.